Erodibility and runoff potential of laterite soils under simulated rainfall conditions - SAJEENA S; Er. E. K Kurien (Guide) (Tavanur 1999 Kelappaji College of Agricultural Engineering and Technology)
Erodibility and runoff potential of laterite soils under simulated rainfall conditions
Erodibility and runoff potential of laterite soils under simulated rainfall conditions